Computation of regular friends for output-nulling and reachability subspaces of linear time-invariant descriptor systems - Kazantzidou, C.; Ntogramatzidis, Lorenzo; Perez, T. (2018)
© 2018 European Control Association (EUCA). In this paper, we employ the Rosenbrock system matrix pencil to find and parameterise regular friends of output-nulling and reachability subspaces of linear, time-invariant descriptor systems, which yield nonzero characteristic polynomial and assign the corresponding closed-loopfinite eigenstructure. In particular, we consider impulse controllable descriptor systemsand the computation of these friends is done in such a way to also eliminate impulsive behaviour.